MANAJEMEN KEGIATAN EKSTRAKULIKULER PRAMUKA SEBAGAI UPAYA PENGEMBANGAN POTENSI KEPEMIMPINAN SISWA SD BUMI QUR’AN DAN SDN SIRNABAKTI - Asep Mulyana; Dewi Maria; Sarah Adawiyah; Hima Alawiyah; Alvina Putri Sukmana; Supyan Sauri (STKIP Subang, 2026)
This study aims to describe and analyze the management of character value-based extracurricular activities as an effort to develop students' leadership potential at SD Bumi Qur’an and SDN Sirnabakti. The study employed a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation studies, and then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing and verification. The results show that extracurricular management in both schools has implemented the POAC stages (planning, organizing, actuating, controlling), albeit with different characteristics tailored to each school's context. SD Bumi Qur’an emphasizes religious values and exemplary behavior, whereas SDN Sirnabakti places greater emphasis on mutual cooperation (gotong royong) and social collaboration. The implementation of scouting (Pramuka) activities has proven to be an effective means of fostering discipline, responsibility, cooperation, and leadership skills. However, the evaluation of student leadership has not been systematically documented. This study concludes that well-planned and character-based management of extracurricular activities can enhance students' leadership potential through habituation, role experience, and direct mentoring from instructors. The study recommends strengthening character-indicator-based planning, instructor training, developing leadership evaluation instruments, and fostering more intensive collaboration with parents and the community.